Rhamnolipids induce oxidative stress responses in cherry tomato fruit to Alternaria alternata. Issue 8 (12th November 2015) - Yan, Fujie; Hu, Hao; Lu, Laifeng; Zheng, Xiaodong
Abstract: BACKGROUND: Rhamnolipids showed an antimicrobial activity applicable to a variety of pathogenic microorganisms, but mechanisms were mostly focused on their direct inhibitory effect. RESULTS: This study showed that disease incidence obviously decreased when cherry tomatoes were treated with rhamnolipids, whether before or after Alternaria alternata inoculation. The activities of antioxidant enzymes, including superoxide dismutase and catalase, were increased in rhamnolipid‐pretreated cherry tomato inoculated with A. alternata within 12 h, while contents of reactive oxygen species decreased. Moreover, resistant response of cherry tomato treated with rhamnolipids and A. alternata was also attributed to activity stimulation of ascorbate peroxidase and glutathione reductase, accompanied with an increase in reduced glutathione, which is beneficial for scavenging excessive H2 O2 . CONCLUSION: Results indicated that rhamnolipids could effectively reduce fungal disease of harvested cherry tomato by inducing fruit resistance and mechanisms involved in elicitation of antioxidative reactions such as the ability to scavenge excess reactive oxygen species. © 2015 Society of Chemical Industry